Social Justice, Sport, and Sociology A Position Statement - Darnell, Simon C.; Millington, Rob (2019)
Amidst widespread inequality, advocates of sport and physical activity have proposed ways in which sport might support those on the social, economic, and geographic margins. In this essay, we consider the place and role of sport in responding to various forms of inequality, and reflect upon its place in pursuing social justice. In so doing, we bring a perspective of critical sociology to the question(s) of whether and how sport can play a role in responding to inequality. Our main argument is that sport has had, and continues to have, a place and role in the pursuit of social justice, but only in so far as sport’s advocates are willing and able to differentiate between justice and charity. To build this case, we draw on the differentiation between the dominant and transformative models of sport for development.
Keywords: Sport; Charity; Development; Inequality; Justice